Effect of Using Cooperative Model Think Talk Write Type and Think Pair Share Type with Talking Stick Strategy on Student Learning Outcomes - Nur Istiqomah, Shara (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to determine the effect of using the cooperative model of the think talk write type and the think pair share type with the talking stick strategy on the geography learning outcomes of students in class X IPS SMA N 1 Banyudono in the 2016/2017 academic year (subject matter of inland waters and their potential). Methodology: This research is a quasi-experimental research (Quasi Experiment) with Posttest only control design. The population in this study was class X IPS SMA N 1 Banyudono in the 2016/2017 academic year. The research sample was taken using the Cluster Random Sampling technique with three times taking from the population and obtained class X IPS 4 as the experimental class 1 (defined as the TTW Learning Method with the TS strategy), class X IPS 2 as the experimental class 2 (defined as the TPS Learning Method with the TS strategy ), and class X IPS 5 as the control class (defined as Group Discussion Method). Data collection techniques using tests, documentation and observation. The data analysis technique is parametric inferential statistics with hypothesis testing using one way Anava (one way Anava) and followed by a post Anava test (Scheffe' test) with a significant level of 5%. Main Finding: There are differences in geography learning outcomes between the use of the TTW type cooperative learning model and the TS strategy, the TPS type and the TS strategy and group discussions with a mean score ratio of 20.69; 19.39; 18.12 and proven by the one-way anava test with a significant level of 5% obtained Fcount>Ftable (6.22706>3.08). The TTW type of cooperative learning model with the TS strategy (20.69) is better than the TPS type with the Talking Stick strategy (19.39). The TTW type cooperative learning model with the TS strategy (20.69) is better than group discussions (18.12). TPS type cooperative learning model with TS strategy (19.39) is better than group discussion (18.12). The three learning models have different qualities, the learning model that has the greatest influence is the TTW model with the TS strategy, followed by the TPS model with the TS strategy and group discussions. Novelty/Originality of this study: The cooperative model of the think talk write type and the think pair share type with the talking stick strategy on the learning outcomes of students' geography.